MARRIAGE RIGHTS OF AFGHAN WOMEN IN TRADITIONAL PRACTICES AND LEGISLATION PROTECTION - Muhammad Aunurrochim Mas’ad; Mariam Saidona Tagoranao; Hekmatullah Muradi; Faiz Murad (Universitas Islam Negeri Jakarta, 2014)
Marriage Rights of Afghan Women in Traditional Practices and Legal Protection. This paper aims to reviewthe role of law for equal protection of women inAfghanistan and offers recommendations so that their marriage rights areprotected by civil law. Although the civil law of Afghanistanmentions guarantees and protections of marriage rights of women, however, they are still at risk of being subjected to harmfultreatment, customs, or traditions which are practiced in Afghanistan. Therefore, this paper is important in finding a solution to theproblems of women in Afghanistan until they obtain duly protectedrights by law.DOI: 10.15408/ajis.v14i2.1278